2016
DOI: 10.12968/jowc.2016.25.8.438
|View full text |Cite
|
Sign up to set email alerts
|

Exploring nurses' and patients' feelings of disgust associated with malodorous wounds: a rapid review

Abstract: ObjectiveTo identify primary empirical research related specifically to feelings of disgust associated with malodorous chronic cutaneous wounds. MethodsA rapid review of the literature using the key words disgust; wounds; malodour and psychosocial. ResultsA total of 163 papers were retrieved with 7 papers being included for the final review. Themes emanating from the review were malodour, healthcare professionals coping with malodour and disgust. Malodour is a concern to patients which can sometimes go unrepor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…However, further research is needed to establish the relative importance of disgust traits in explaining depression compared to other physical factors, such as pain or itch, and other psychosocial factors, such as stigma, social isolation, and coping behaviours. There is evidence that malodorous cutaneous conditions, such as an infected wound, trigger disgust (Ousey & Roberts, 2016), but future research could usefully explore which aspects of skin conditions are the strongest triggers for disgust and how to help people manage these aspects.…”
Section: Discussionmentioning
confidence: 99%
“…However, further research is needed to establish the relative importance of disgust traits in explaining depression compared to other physical factors, such as pain or itch, and other psychosocial factors, such as stigma, social isolation, and coping behaviours. There is evidence that malodorous cutaneous conditions, such as an infected wound, trigger disgust (Ousey & Roberts, 2016), but future research could usefully explore which aspects of skin conditions are the strongest triggers for disgust and how to help people manage these aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies identified malodor as especially distressing for nurses. 5,65,66,69,70 Its impact negatively affected the nurse-patient relationship and threatened the trust relationship between the nurse and the patient. 69 Nurse respondents reported using various strategies to cope with these typically malodorous wounds such as changing their breathing pattern, meticulous hand hygiene after tropical or physical care, and scheduling care for patients with MFW around the end of their shift.…”
Section: Nurse and Caregiver Experiences Related To Mfwmentioning
confidence: 99%
“…Das exulzerierende Tumorwachstum führt zu einer einschneidenden Veränderung des Körperbildes bis hin zu Entstellungen. Begleitende Symptome wie Wundgeruch und Exsudation führen zu Unsicherheit, Scham und auch Ekel und können zu sozialem Rückzug führen [1206,1207]. Durch die Wunde und damit das Sichtbarwerden der lebensbegrenzenden Erkrankung kann es zu vielfältigen emotionalen Reaktionen wie Angst, Verleugnung, Ärger/ Wut und Depression kommen [1208], [1209].…”
Section: Hintergrundunclassified
“…Bei Teammitgliedern, vor allem Pflegefachpersonen, die für die Wundversorgung der Menschen mit malignen Wunden direkt zuständig sind, kann es durch die Konfrontation mit dem Anblick der Wunde, den Gerüchen und dem Exsudat sowie dem entstellten Körperbild zu eigenen emotionalen Resonanzen wie Ekel, Abscheu und Berührungsängsten aber auch Mitgefühl/ -leid kommen [1207,1220,1293]. Daher ist der Rückhalt im Team wichtig: belastete Kollegen können im Team aufgefangen, unterstützt und bestärkt werden, ihre eigenen Grenzen zu erkennen, zu respektieren und zu akzeptieren [1294].…”
Section: Hintergrundunclassified